KEPERCAYAAN AKSEPTOR KB WANITA DENGAN PEMILIHAN METODE KONTRASEPSI DI DESA LOK BESAR WILAYAH KERJA PUSKESMAS BIRAYANG KABUPATEN HULU SUNGAI TENGAH - Herawati; Nurmayanti, Dewi Risma; Ramie, Agustine (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2017)
Selection of contraceptive method is influenced by several factors, one of which was the intentionarising from the attitude based on the belief, the rules in society and the basic rules that exist inthe environment. The purpose of this research was to know the relation of belief woman KBacceptor with the contraception method selection in Lok Besar Village work area of PuskesmasBirayang of Hulu Sungai Tengah Regency. This research used analytic observational methodwith cross sectional approach. Respondents amounted to 66 people taken by simple randomsampling with instruments in the form of a questionnaire of women's KB acceptor trust andchecklist of selection of contraceptive method. Research showed that positive female familyplanning acceptor acceptance was 48 people (72,7%) and negative woman acceptor acceptanceis 18 people (27,3%). Data analysis result of this research using Fisher's Exact Test obtained pvalue = 1,000, α = 0,10, meaning there is not relation of belief of woman KB acceptor withselection of contraception method in Lok Besar Village work area of Puskesmas Birayang ofHulu Sungai Tengah Regency. The beliefs of female FP acceptors are not related to the choice ofcontraception methods. For female KB acceptor to increase awareness in contraception, eitherLTCM or Non-LTCM contraception.